Blended Nanoparticle System Based on Miscible Structurally Similar Polymers: A Safe, Simple, Targeted, and Surprisingly High Efficiency Vehicle for Cancer Therapy. Issue 8 (19th March 2015) - Tao, Wei; Zhang, Jinxie; Zeng, Xiaowei; Liu, Danny; Liu, Gan; Zhu, Xi; Liu, Yanlan; Yu, Qingtong; Huang, Laiqiang; Mei, Lin
<x xml:space="preserve">Abstract</x> A novel blended nanoparticle (NP) system for the delivery of anticancer drugs and its surprisingly high efficacy for cancer chemotherapy by blending a targeting polymer folic acid‐poly(ethylene glycol)‐b‐poly(lactide‐co‐glycolide) (FA‐PEG‐b‐PLGA) and a miscible structurally similar polymer D‐α‐tocopheryl polyethylene glycol 1000 succinate‐poly(lactide‐co‐glycolide) (TPGS‐PLGA) is reported. This blended NP system can be achieved through a simple and effective nanoprecipitation technique, and possesses unique properties: i) improved long‐term compatibility brought by PEG‐based polymers; ii) reduced multidrug resistance mediated by P‐glycoprotein (P‐gp) in tumor cells and increased bioavailability of anticancer drugs by incorporation of TPGS; iii) the regulation of controlled release through polymer ratios and active targeting by FA. Both in vitro cell experiments and in vivo antitumor assays demonstrated the reported blended NP system can achieve the best therapeutic efficiency in an extremely safe, simple and highly efficient process for cancer therapy. Moreover, this NP system is highly efficient in forming NPs with multiple functions, without repeated chemical modification of polymers, which is sometimes complex, inefficient and high cost. Therefore, the development of this novel blended NP concept is extremely meaningful for the application of pharmaceutical nanotechnology in recent studies.